Patients with hereditary hemorrhagic telangiectasia have increased plasma levels of vascular endothelial growth factor and transforming growth factor-β1 as well as high ALK1 tissue expression - Sadick, Haneen; Riedel, Frank; Naim, Ramin; Gößler, Ulrich; Hörmann, Karl; Hafner, Mathias; Lux, Andreas (Haematologica, the hematology journal, 2005)
BACKGROUND AND OBJECTIVES: Hereditary hemorrhagic telangiectasia (HHT), an inherited vascular dysplasia, is caused by mutations in endoglin or activin receptor-like kinase (ALK)-1. Haploinsufficiency for these genes is thought to result in an imbalanced angiogenic activity. The aim of this study was to evaluate the plasma levels and the expression profiles of angiogenic and angiogenesis-related factors in the context of HHT. - DESIGN AND METHODS: Vascular endothelial growth factor (VEGF) and transforming growth factor (TGF)-beta1 plasma concentrations were determined in 31 HHT patients and 40 healthy controls by ELISA. VEGF and TGF-beta1 plasma concentrations were correlated with the patients' clinicopathological features. Tissue expression of angiogenic and angiogenesis related proteins was determined by immunostaining on nasal cryostat sections from 13 HHT patients and 5 healthy controls. - RESULTS: Of the 31 patients, 29 had statistically significantly raised plasma concentrations of VEGF and TGF-beta1 but there was no correlation with specific clinicopathological features. Increased VEGF, TGF-beta1 and ALK1 immunostaining was seen in all 13 investigated patients. beta-smooth muscle actinin immunostaining was increased in 12 patients. Increased endoglin immunostaining was seen in only 9 patients. - INTERPRETATION AND CONCLUSIONS: This study provides evidence of the role of VEGF and TGF-beta1 in the pathogenesis of HHT. Plasma concentrations of these two factors may serve as further diagnostic criteria for HHT. For the first time, we report increased TGF-beta1 plasma concentrations and increased TGF-beta1 and ALK1 tissue expression in HHT, which appear not to be specifically associated with either endoglin or ALK1 mutations. The data suggest that HHT is an angiogenic disorder characterized by an over-expression of VEGF, TGF-beta1 and ALK1.